2016
DOI: 10.4269/ajtmh.15-0714
|View full text |Cite
|
Sign up to set email alerts
|

Case Series of Imported Enteric Fever at a Referral Center in Tokyo, Japan: Antibiotic Susceptibility and Risk Factors for Relapse

Abstract: Abstract. Owing to the increase in Salmonella strains with decreased fluoroquinolone susceptibility in the endemic areas, we have been treating enteric fever with intravenous ceftriaxone empirically since 2007. In this study, we reevaluated our treatment protocol. This retrospective cohort study was conducted at a single institute in Tokyo, Japan, between January 2006 and December 2013. Enteric fever was defined as isolation of Salmonella Typhi or Salmonella Paratyphi A, B, and C from the blood and/or stool of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 28 publications
(32 reference statements)
0
6
0
Order By: Relevance
“…Contrary to the current research on antibiogram of S . Typhi, the bacterium is showing full sensitivity to these antibiotics since they had not been used for a long time to treatment typhoid fever [ 21 ]. A study in Nepal reported an increased susceptibility rate of chloramphenicol, co-trimoxazole, and ampicillin as 98.8, 98.8, and 97.6% respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to the current research on antibiogram of S . Typhi, the bacterium is showing full sensitivity to these antibiotics since they had not been used for a long time to treatment typhoid fever [ 21 ]. A study in Nepal reported an increased susceptibility rate of chloramphenicol, co-trimoxazole, and ampicillin as 98.8, 98.8, and 97.6% respectively [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…The delay in starting typhoid fever treatment and the longer the time to decrease body temperature (> 7 days) can affect patient recurrence and will lead to increased treatment costs due to the longer hospitalization time. 14,15 The condition of the patients when they left the hospital did not die or go home at their own request, but with the condition of outpatient treatment with the approval of the doctor. Typhoid fever patients who are declared cured or improved must perform a bacteriological examination at least once a month to detect Salmonella typhi bacteria because these bacteria can still be excreted by the body within 3 months or more than a year.…”
Section: Discussionmentioning
confidence: 99%
“…Typhoid fever patients who are declared cured or improved must perform a bacteriological examination at least once a month to detect Salmonella typhi bacteria because these bacteria can still be excreted by the body within 3 months or more than a year. 15 The fluoroquinolone class of antibiotics (ciprofloxacin, levofloxacin, pefloxacin and ofloxacin) is an effective therapy for typhoid fever in isolates that are not resistant to fluoroquinolones. This class of antibiotics has a clinical cure rate of up to 98%, a recurrence rate and fecal career of less than 2%, and a fever reduction time of 4 days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this scenario, it is alarming that relapse caused by drug-susceptible isolates is reported in the order of 5%–15% by many studies. 7 , 8 Intracellularity as a lifestyle therefore impacts the antimicrobial chemotherapy of S. enterica infections.…”
Section: Introductionmentioning
confidence: 99%